Waterborne exposure to bisphenol F causes thyroid endocrine disruption in zebrafish larvae. (March 2016) - Huang, Guo-min; Tian, Xiao-feng; Fang, Xue-dong; Ji, Fu-jian
Abstract: While bisphenol F (BPF) has been frequently detected in various environmental compartments, limited information is available on its effect on thyroid endocrine system. In the present study, zebrafish ( Danio rerio ) embryos were exposed to 0.2, 2, 20, and 200 μg/L of BPF from 2 h post-fertilization (hpf) to 144 hpf. The whole-body content of thyroid hormones, thyroid-stimulating hormone (TSH), and transcription of genes belonging to the hypothalamic-pituitary-thyroid (HPT) axis were investigated. BPF exposure resulted in alterations of both T3 and T4 contents, increased the ratios of T3/T4, demonstrating thyroid endocrine disruption. Moreover, TSH content was significantly induced in a concentration-dependent manner after exposure to BPF. The increased gene transcription of dio2 might assist to degrade increased T3 contents. Treatment with BPF also significantly increased transcription of genes involved in thyroid hormone regulation ( crh ) and synthesis ( nis and tg ) as a compensatory mechanism for the decrease of T4 contents. However, the gene encoding protein involved in TH transport ( ttr ) was transcriptionally significantly down-regulated after exposure to BPF. Taken together, these results suggest that BPF alters the transcription of genes involved in the HPT axis as well as changes whole-body contents of thyroid hormones and TSH in zebrafish embryos/larvae, thus causing an endocrine disruption of the thyroid system. Highlights: As a functional substitute of BPA, BPF has been widely used in daily life, and was detected in various environmental media. Zebrafish embryos were exposed to different concentrations of BPF for 6 days. BPF exposure resulted in increase of TSH contents in zebrafish larvae. BPF altered both T4 and T3 contents, disturbed the homeostasis of THs, thus exerting thyroid endocrine disruption. Genes involved in HPT axis were also modulated after BPF exposure.